2011
DOI: 10.1002/jhm.1003
|View full text |Cite
|
Sign up to set email alerts
|

Serial administration of a modified richmond agitation and sedation scale for delirium screening

Abstract: Objectives Because delirium is common and frequently unrecognized, this study sought to design a brief screening tool for a core feature of mental status and to validate the instrument as a serial assessment for delirium. Design Prospective cohort Setting Tertiary VA Hospital in New England Participants 100 Veterans admitted to the medical service Methods A consensus panel developed a modified version of the Richmond Agitation and Sedation Scale (RASS) to capture alterations in consciousness. Upon admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 13 publications
4
115
2
3
Order By: Relevance
“…In 95 older medical inpatients, Chester et al observed that a mRASS other than 0 was 64% sensitive and 93% specific for delirium. 8 A mRASS > +1 or < −1 was 34% sensitive and 100% specific for delirium. 8 They reported a weighted kappa of 0.48.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In 95 older medical inpatients, Chester et al observed that a mRASS other than 0 was 64% sensitive and 93% specific for delirium. 8 A mRASS > +1 or < −1 was 34% sensitive and 100% specific for delirium. 8 They reported a weighted kappa of 0.48.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have evaluated the RASS in hospitalized medical and hip fracture patients, but have limited generalizability to the older ED patient population, who include both admitted and discharged patients. 8,9 The purpose of this study was to determine the diagnostic accuracy of the RASS for delirium in older ED patients.…”
Section: Introductionmentioning
confidence: 99%
“…The Modified Richmond Agitation and Sedation Scale (mRASS), which measures arousal, sedation and level of consciousness, has been advocated as a screening tool for delirium. However, the mRASS has a low sensitivity of 64% to70%, 42, 43 and the usefulness of the scale depends on the prevalence of decreased mental status in the population. In settings with high prevalence of sedation and depressed sensorium, such as the postoperative recovery room and ICU, this approach may be valuable; however, routine use of the mRASS is not recommended outside of these settings, since many cases of delirium will be missed.…”
Section: Resultsmentioning
confidence: 99%
“…The m-RASS has a sensitivity of 64% and a specificity of 93% for delirium. 1 However, its greatest value lies in its ability to monitor patients over time and identify changes; serial m-RASS measurements used to detect changes have a sensitivity of 85% and a specificity of 92% for incident delirium.…”
mentioning
confidence: 99%